Information avoidance, selective exposure, and fake (?) news: theory and experimental evidence on green consumption - Momsen, Katharina; Ohndorf, Markus (Journal of economic psychology, 2022)
We investigate self-serving information avoidance by consumers when revelation is stochastic and the revealed information is potentially erroneous. Our formal considerations based on a cognitive dissonance model suggest that the size of the price difference between product options determines if information avoidance arises. This prediction is supported by our laboratory experiment, in which subjects purchase products associated with co-benefits implemented as contributions to climate change mitigation. In seven treatments, we alter the information structure as well as the perceived revelation costs. We find robust evidence of self-serving information avoidance in treatments with simple stochastic revelation and reduced reliability of information, representing potential ‘fake’ news. The propensity to avoid information increases with the introduction of merely nominal information costs. In contrast to previous studies, we conclude that self-serving information avoidance can arise in consumption, which could also explain the persistent demand for products associated with ‘green-washing’.